Modelling of improved LSTM +1D convolution neural network methods for the diagnosis of SKF bearings - Feudjeu Josias Éric , Signe; Wolfgang, Nzié; Djami Aslain Brisco , Ngnassi; Eloundou Pascal , Ntsama; Priva , Chassem (International Journal of Engineering and Technology, 2024)
The ability to accurately detect and predict faults in automotive bearings is essential for diagnostic applications in the maintenance process. Although previous methods can accurately identify the various faults on bearings, they mostly produce erroneous results in the presence of certain mechanical factors when classifying the data. We propose a new diagnostic framework based on one-dimensional convolutional neural network (CONV1D) modelling and improved long short-term memory (LSTM), together with confusion matrices to evaluate data classification using the Deep Learning algorithm. Our framework classifies the data by taking into account the mechanical factors of the bearings (sudden load, rotation speed, operating temperature, etc.). Our results improve the training accuracy of the model to over 96.6%, with a percentage error of 23.29% for 50 iterations (repetitions). This percentage of training accuracy could be closer to 100% and that of the error margins to 0% if we increase the number of iterations. These results underline the promise of our method across our model and indicate how future expansion of the model by combining three methods can lead to further improvements in training accuracy with fewer errors and fewer iterations.